A Study on the Effects of Hob Temperature on the Rock-Breaking Characteristics of Sandstone Strata - Yun-Gui Pan; You-Liang Chen; Xi Du; Hui-Dong Tong; Fei-Yu Tang; Xiao-Jian Wu; Su-Ran Wang; Shao-Ming Liao; Bin Peng (Applied Sciences, 2024)
To explore the effect of hob temperature on the rock-breaking characteristics of full-section tunnel boring machines (TBMs) in sandstone strata, high-temperature furnace heating experiments of sandstone and physical and mechanical experiments at room temperature and high temperatures were conducted to obtain the mechanical properties of sandstone at different temperatures. The mechanical properties at different temperatures were calibrated using PFC3D to obtain micro-mechanical and thermodynamic parameters and establish a rock-breaking model. The orthogonal experiments were used to establish the simulation experiments of rock breaking under different temperatures, confining pressure conditions, knife tip distances, and penetration degrees. The results show that the hob tip force is gradually increasing with an increase in the confining pressure. When below 600 °C, there is little temperature transfer from particle to particle as the temperature increases. At this time, with the two sides of the rock slag flaking, the hob knife tip force is the first to reduce. After 600 °C, with the expansion of the rock extrusion hob, the temperature rises on both sides; at this time, the hob tip force also increased. The hob tip force is minimal at a tip distance of 70 mm and an S/P of 14. As the surrounding pressure increases, the rock-breaking efficiency of the hobber decreases. The highest rock-breaking efficiency is achieved at 25 °C and 600 °C. The rock-breaking efficiency is highest when the knife tip distance is designed to be 70 mm, and when the S/P is 14. The three-dimensional constitutive analysis of rock-breaking particles showed that the increment caused by the hob temperature is mainly distributed in the normal force direction in the surrounding rock without any confining pressure, and the increment caused by the hob temperature exposed to the confining pressure occurs in all directions.